Optimization of Rotary Degassing Parameters to Improve Melt Cleanliness and Mechanical Properties in A356 Aluminum Alloy - Kutsal, U.; Çolak, M.; Sağnak, Y.; Bardakcı, S.; Ammas, G.; Sarper, G. (Archives of Foundry Engineering, 2026)
Melt cleanliness is a critical factor that directly affects the quality of aluminum castings and becomes even more significant in recycling-oriented production, where high scrap utilization is inevitable. Increasing the proportion of scrap intensifies the risk of oxide films, inclusions, and gas porosity in the molten metal; therefore, efficient refining techniques are essential. In this study, the effects of rotary degassing parameters—including rotor speed, rotation time, and gas flow rate—on melt cleanliness of A356 aluminum alloy were systematically investigated. Experimental melts containing 20% primary and 80% scrap aluminum were treated under various degassing conditions using a commercial flux cleaning flux. Characterization was performed through the Reduced Pressure Test (RPT), bifilm index analysis, fluidity measurements, microstructural examinations, and mechanical testing (tensile test and Brinell hardness measurement). The results demonstrated that increasing the rotor speed from 200 rpm to 500 rpm significantly reduced both the density and bifilm indices, indicating a notable improvement in melt cleanliness. Furthermore, higher gas flow rate (10 L/min) and longer rotation time (10 min) provided additional but secondary improvements. Consequently, the optimization of rotary degassing parameters enhanced not only melt quality but also tensile strength and ductility. These findings offer practical insights for optimizing process control in recycling-based aluminum foundries.